2001
DOI: 10.1021/jp003541j
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of Formic Acid vs Formate and Ethanol vs Ethoxy on TiO2 and Effect of Adsorbed Water on the Rates of Formate and Formic Acid Photooxidation

Abstract: Comparison of photooxidation rates of formic acid and formate on TiO 2 as well as the effect of adsorbed water on formate and formic acid photodecomposition rates have been investigated by Fourier transformed infrared spectroscopy. Adsorbed formic acid and formate are all photooxidized to CO 2 in O 2 . Formic acid on TiO 2 shows a photoreaction rate that is roughly 53 times that of formate groups for a same surface concentration. The presence of H 2 O can increase formate and formic acid photooxidation rates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 34 publications
8
131
2
Order By: Relevance
“…(1720 cm −1 ) forms [26]. Based on the above results, we suggest that we now have a polymeric titanuim acetate, such as Ti[(OH) y (OOCCH 3 ) x ] much less reactive species, with x and y between 0 and 2, from which all OC 3 H 7 groups have completely disappeared (942 cm −1 ) [27].…”
mentioning
confidence: 60%
“…(1720 cm −1 ) forms [26]. Based on the above results, we suggest that we now have a polymeric titanuim acetate, such as Ti[(OH) y (OOCCH 3 ) x ] much less reactive species, with x and y between 0 and 2, from which all OC 3 H 7 groups have completely disappeared (942 cm −1 ) [27].…”
mentioning
confidence: 60%
“…6 Formate adsorption on TiO 2 has been studied extensively. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Previous studies of adsorption of formic acid (HCOOH) on rutile TiO 2 (110) surfaces have shown that upon adsorption it dissociates into a formate ion (HCOO -) and a proton (H + ), which bind to lowcoordinated Ti and O surface atoms, respectively. 22,23 The adsorption structure of small molecules, such as HCOOH, can be studied favourably by infrared spectroscopy, and in particular infrared reflection-absorption spectroscopy (IRRAS) has been employed to study e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the spectra taken before and after the indicated times during photoirradiation of adsorbed CH 2 [14]. Likewise, photooxidation of HCOO (a) on TiO 2 in O 2 produces CO 2 [11]. Figure 6 shows the spectra taken before and after the indicated times during photoirradiation of a …”
Section: Methodsmentioning
confidence: 99%